The early history of netting bats - Timm, Robert M.; McLaren, Suzanne B; Genoways, Hugh H. (THERYA, 2021)
The Japanese-style mist net that mammalogists and ornithologists use extensively came into regular use by scientists in the 1950s and early 1960s and its use in capturing bats and birds unharmed is now worldwide. The history of the innovative mist net, which was originally made of silk and brought to the U.S. by ornithologist Oliver L. Austin, Jr., shortly after WW II, was reviewed recently by Genoways et al. (2020). However, the mist net was not the first net to be used for the scientific capture of bats and birds—that was the Italian trammel net.